Spirituality and hospice social work - Callahan, Ann M. (End-of-life care, 2017)
Champion of spiritual care -- Spiritual diversity -- Spiritual needs -- Spiritual suffering -- Relational spirituality -- Spiritual care -- Spiritual sensitivity -- Spiritual competency